P4.079 Sexual Behaviors and Safety Strategies of Women Who Have Sex with Men and Women. (13th July 2013) - Schick, V R; Bell, A; Neal, C; Pol, B Van Der; Dodge, B; Bay-Cheng, L; Fortenberry, J D
Abstract : Background: Women who have sex with women and men (WSWM) are at an increased risk for STI. Yet, knowledge regarding the behaviours associated with infection remains limited, with most studies focused on the experiences of women who have sex with only men or women. The diversity of sexual behaviours WSWM engage in may be limited by comparing WSWM to other groups. Instead, focusing on their experiences exclusively may provide a more comprehensive understanding of the sexual lives of WSWM. Methods: Local (Indianapolis, IN, US) women who had engaged in recent genital contact with a male and female partner were invited to complete an on-line survey followed by an interview. Participants were asked to indicate the most recent time they had participated in a variety of behaviours with a male and/or female partner. Results: Eighty participants ranging in age from 18 to 51 (M = 26.74, SD = 7.97) completed the survey. The most commonly reported sexual behaviours were similar for male and female partners, including kissing, cuddling, external genital rubbing, vaginal fingering, cunnilingus/fellatio and penile-vaginal intercourse. While less commonly reported, a sizable minority of participants reported vaginal fisting, anal fingering and analingus. Toy use was reported by the majority of the participants with vibrator use reported as the most commonly used toy. Approximately 75% of participants indicated sexual behaviour with more than one person at one time. The percentage of participants who reported barrier use varied by behaviour and partner gender with the lowest percentage of participants reporting use during oral sex or genital-on-genital rubbing with a female partner (> 90% never) and the highest percentage reporting use during penile-vaginal intercourse (> 25% always). Conclusion: Participants reported engaging in a variety of sexual behaviours that may facilitate STI transmission. Further knowledge about the types of behaviours WSWM engage in may help inform risk reduction strategies.